Comparison of the effects of Lactobacillus plantarum versus imipenem on infected burn wound healing - Soleymanzadeh Moghadam, Somayeh (Iran University of Medical Sciences, 2020)

(untitled) (Med J Islam Repub Iran)
Background: Infection of burn wounds is one of the most important problems in the world. Lactobacillus plantarum is known for burn wound healing because of the immunomodulatory and anti-microbial roles. This study was performed to compare the effects of L. plantarum and imipenem – alone and in combination – on infected burn wound healing. Methods: Burn wounds were experimentally induced on 50 rats in three test groups (germ and supernatant of L. plantarum ) and two control groups (n=10 each) and were inoculated with Pseudomonas aeruginosa. During a 14-day period, wounds in all groups were daily treated topically. The data were analyzed using one-way analysis of variance followed by Tukey–Kramer and LSD. A p-value of < 0.05 was considered as statistically significant. Results: The mean size of the wound on day 14 after the treatment in the probiotic group was significantly lower than the control and the supernatant treated groups (p<0.05). The percentage of wound healing was significantly higher in the probiotic pellet treated group compared to the imipenem and the supernatant groups (by Anova test: 69.58%, p=0.022). The mean leukocyte count in the probiotic pellet group (12110) and supernatant group (13650) was significantly higher than the imipenem group (7670) (p=0.002 and 0.001, respectively). Wound cultures revealed that the percentage of cases where the pathogens had no growth was significantly different among the comparison groups. In all three test groups, P. aeruginosa was completely eliminated in comparison to the positive control group (p<0.05). Conclusion: The results of our study showed that L. plantarum and its by-products promote wound healing and can be used as an alternative to antibiotics to treat ulcer infections caused by resistant bacteria.